Associations between anxiety, depression, and personal mastery in community-dwelling older adults: a network-based analysis - Zekun Bian; Renyan Xu; Bin Shang; Fei Lv; Weiyi Sun; Qian Li; Yijing Gong; Caifeng Luo (BMC Psychiatry, 2024)
Abstract Background In China, about 18.70% of the population aged 60 years and older are at risk of low personal mastery as well as anxiety and depression for a variety of reasons. The purpose of this study was to construct a symptom network model of the relationship between anxiety, depression, and personal mastery in community-dwelling older adults and to identify central and bridge symptoms in this network. Methods Depression, anxiety, and personal mastery were measured using the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder Scale (GAD-7), and Personal Mastery Scale (PMS), respectively. A total of 501 older adults in 16 communities in Changzhou and Zhenjiang, Jiangsu Province, China, were surveyed by using a combination of stratified sampling and convenience sampling methods. The R language was used to construct the network. Results (1) The network structure of anxiety–depression–personal mastery was stable, with “Nervousness” (node GAD1, strength = 1.38), “Sad mood” (node PHQ2, strength = 1.22), " Inability to change” (node PMS2, strength = 1.01) and “Involuntarily” (node PMS3, strength = 0.95) as the central symptoms. (2) “Irritability” (node GAD6, bridge strength = 0.743), “Sad mood” (node PHQ2, bridge strength = 0.655), and “Trouble relaxing” (node GAD4, bridge strength = 0.550) were the bridge symptoms connecting anxiety, depressive symptoms, and personal mastery. (3) In the network comparison test (NCT), residence, somatic chronic comorbidity and gender had no significant effect on network structure. Conclusions The construction of the anxiety–depression–personal mastery network structure opens up new possibilities for mechanisms of action and intervention formulation for psychological disorders in community-dwelling older adults. The identification of central symptoms (e.g., nervousness, sad mood, inability to change, involuntarily) and bridge symptoms (e.g., irritability, sad mood, trouble relaxing) in community-dwelling older adults with anxiety, depression, and low sense of mastery can provide a scientific basis for the development of precise interventions.